miR-152 Attenuates Apoptosis in Chondrocytes and Degeneration of Cartilages in Osteoarthritis Rats via TCF-4 Pathway - Daqian Wan; Yang Qu; Songtao Ai; Liming Cheng (SAGE Publishing, 2020)
Introduction: Osteoarthritis (OA) is associated with deregulation of various miRNAs (miRs). The present study reported protective effect of miR-152 in osteoarthritis. Methods: Tissue cartilage tissues of OA and normal subjects were used, rat model of anterior cruciate ligament transection (ACLT) was developed. Cartilage study was done by Safranin O-fast green, histological and immunostaining. The chondrocytes were isolated from tissues and were treated with IL-1β and infected with miR-152 or TCF-4 cloned lentiviral vectors. MTT assay was done for cell viability, apoptosis by Annexin-V-FITC staining. Expressions of proteins by western blot assay. Collagen-II assay was done by immunofluroscent assay. Luciferase activity by dual luciferase reporter assay. Results: Upregulation of miR-152 improved viability of chondrocytes, decreased apoptosis and balanced the catabolic and anabolic factors of extracellular matrix in vitro. Injecting miR-152 lentivirus in rats improved articular cartilage in osteoarthritis ACLT rats. Bioinformatics analysis suggested TCF-4 as favorable target gene of miR-152, having binding site on the 3'UTR region of TCF-4 mRNA and inhibited the expression of TCF-4. Osteoarthritis tissue cartilage both from humans and rats showed expression of miR-152 inversely linked with expression of TCF-4. Conclusion: Present study concludes miR-152 diminished the progression of osteoarthritis partially by inhibiting the expression of TCF-4.